P1-S5.29 Relationship between incident bacterial vaginosis, gonorrhoea and chlamydial infection among women attending a sexually transmitted disease clinic. (10th July 2011) - Gallo, M; Macaluso, M; Warner, L; Fleenor, M; Hook, E; Brill, I; Weaver, M
Abstract : Background: Interactions between bacterial vaginosis (BV) and inflammatory sexually transmitted infections, such as gonorrhoea and chlamydial infection, are not well understood. Furthermore, evidence regarding the sexual transmission of BV is equivocal. Methods: We assessed associations between incident BV and incident gonorrhoea and/or chlamydial infection (gonorrhoea/chlamydia), as well as similarities in associations for the two processes, among 645 women attending a sexually transmitted disease clinic in Alabama, who were followed prospectively for 6 months in 1995–1998. We also identified predictors of both incident BV and gonorrhoea/chlamydia and used bivariate logistic regression to determine whether these predictors differed. Results: Participants completed 3188 monthly, follow-up visits. Several factors associated with incident BV involved sexual intercourse: young age (<16 years) at first intercourse (adjusted OR [aOR]: 1.5; 95% CI 1.1 to 1.9), recent drug use during sex (aOR: 1.7; 95% CI 1.2 to 2.5), prevalent trichomoniasis (aOR: 2.8; 95% CI: 1.7 to 4.6) and incident syphilis (aOR: 9.7; 95% CI 1.9 to 48.4). Few statistical differences between potential factors for BV and gonorrhoea/chlamydia emerged. Specifically, in the adjusted bivariate analysis, we found no evidence that the four sex-related risk factors for incident BV (along with unprotected vaginal acts, which was a risk factor for incident gonorrhoea/chlamydia) differed in their associations with the two study outcomes. We found evidence that incident BV preceded the acquisition of gonorrhoea/chlamydia (adjusted pairwise OR [aPOR]: 1.6; 95% CI 1.1 to 2.3), and gonorrhoea/chlamydia appeared to precede the acquisition of BV (aPOR: 2.4; 95% CI 1.7 to 3.5). Conclusions: Study findings provide support for the interpretation that BV is sexually transmitted. We found temporal relationships between BV and gonorrhoea/chlamydia in both directions, which suggests that treating one condition might confer protection against the other. However, this effect needs to be demonstrated in future clinical studies.